Comparación de etomidato, ketamina y propofol como inductores para gastroduodenoscopia en perros (2007)
ABSTRACT: Upper digestive endoscopy (EDS) is a currently used diagnostic method in small animal practice. The procedure requires anesthetics which selection is crucial. This study compared the effects of three of them: etomidate, ketamine and propofol, regarding capacity to facilitate the passage of the endoscope until (or down to) to the duodenum. It was also determined which of these inducers contribute the best to perform the technique in a shorter time, and which one of the protocols leads to a faster recovery. The results indicate that none of the inducers make significantly more difficult the access to the stomach, nor the passage through this organ, although with etomidato the time needed was shorter. There were no differences either in time or difficulty to go through the pylorus. Nevertheless, from the clinical point of view ketamine made this step more difficult. For recovery, propofol did present a significant shorter period (p>0.05). It is concluded that the three studied agents show a similar statistical profile, but from the clinical point of view etomidato behaves better.